Analysis of Organizational Behavior Transformation in the Era of Digitalization and Sustainability at State Universities - Firda Maulani Lestari; Hady Siti Hadijah; Janah Sojanah; Eeng Ahman; Budi Santoso (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study presents a Systematic Literature Review (SLR) on the transformation of organizational behavior in the era of digitalization and sustainability within higher education institutions. Using an SLR approach and systematic searches across academic databases such as Scopus, Google Scholar, and ScienceDirect, ten relevant national and international articles were identified and thematically analyzed. The aim of this review is to explore trends, driving factors, and practical implications of digitalization and sustainability practices on organizational behavior in higher education settings. The findings highlight four interrelated dominant themes: (1) digital leadership that drives organizational culture transformation; (2) adaptive organizational culture that supports innovation and continuous learning; (3) green innovation and green campus initiatives as tangible forms of sustainability; and (4) human resource readiness through enhanced digital literacy. The study emphasizes the importance of integrating digital and sustainability-oriented policies into institutional strategies to foster adaptive, collaborative, innovative, and long-term sustainable organizational behavior within higher education.